Deletion of the donor splice site of intron 4 in the glucokinase gene causes maturity-onset diabetes of the young. - F Sun; B Knebelmann; M E Pueyo; H Zouali; S Lesage; M Vaxillaire; P Passa; D Cohen; G Velho; C Antignac (The Journal of Clinical Investigation, 1993)
Missense and nonsense mutations in the glucokinase gene have recently been shown to result in maturity-onset diabetes of the young (MODY), a subtype of non-insulin-dependent diabetes mellitus with early age of onset. Glucokinase catalyzes the formation of glucose-6-phosphate and is involved in the regulation of insulin secretion and integration of hepatic intermediary metabolism. Nucleotide sequence analysis of exon 4 and its flanking intronic regions of the glucokinase gene, in four hyperglycemic individuals of a MODY family, revealed a deletion of 15 base pairs, which removed the t of the gt in the donor splice site of intron 4, and the following 14 base pairs. This deletion resulted in two aberrant transcripts, which were analyzed by reverse transcription of RNA from lymphoblastoid cells obtained from a diabetic patient. In one of the abnormal transcripts, exon 5 is missing, while in the other, the activation of a cryptic splice site leads to the removal of the last eight codons of exon 4. This intronic deletion in a donor splice site seems to cause a more severe form of glucose intolerance, compared with point mutations described in glucokinase. This might be due to a more pronounced effect on insulin secretion. Images